OPTIMALISASI PENGUASAAN MUFRODAT MELALUI METODE AUDIOLINGUAL PADA SANTRI DISABILITAS MENTAL - Abdulloh, Zidron; Niami , Muhamad Ardha; Kolik, Ilham; Mufida, Fatikhatul; Ahmadiyah, Husna; Astina, Chairani (DAS Institute, 2023)
In this study, the purpose and objectives are to find out how to apply the process of mastering vocabulary to mentally disabled students, optimizing the application of the audiolingual method in mastering Arabic vocabulary to mentally disabled students, factors that influence mastery of vocabulary in using the audiolingual method and solutions that are carried out when encountering obstacles in implementing optimization of mastery of vocabulary through the audiolingual method on mentally disabled students. The research method uses a case study research type with a qualitative descriptive approach. While the data analysis uses qualitative descriptive data analysis by collecting existing facts and then drawing general conclusions. The results of this study conclude that optimizing mastery of vocabulary through the audiolingual method on mentally disabled students can be said to be quite optimal. This is based on how mentally disabled students can follow learning to master vocabulary through the audiolingual method well.